EFFECT OF ACCIDENTAL MATERIALS ON THE PROPERTIES OF CONCRETE - Muhammad Afzal; Muazzam Nawaz; Muhammad Tahir; Muhammad Fayyaz Ahmed; Prof Zia Udin Mian (Spectrum of Engineering Sciences, 2025)
EFFECT OF ACCIDENTAL MATERIALS ON THE PROPERTIES OF CONCRETE